1993
DOI: 10.1016/0969-8051(93)90085-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a nonpeptide carbon-11 labeled substance P antagonist for PET studies

Abstract: CP 96,345 is a nonpeptide high affinity antagonist of the substance P (NK1) receptor. The radiosynthesis of [11C]CP 96,345 suitable for Positron Emission Tomography (PET) applications is described. [11C]CP 96,345 was prepared by O-methylation of a desmethyl precursor via in situ generation of its phenolate salt. The in vivo tissue distribution of [11C]CP 96,345 in guinea pigs (n = 2) at 5 and 30 min was determined. Uptake was low in brain (approximately 0.04% dose/g) and highest (approximately 1-2% dose/g) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…First generation radiotracers were selected from many lead structures, based upon autoradiographic studies of NK1Rs. These compounds were initially investigated in vivo for their ability to be taken up by the brain and other organs in animal models [146,147,148,149] (Figure 4). Early evaluation of [ 11 C]CP-96,345 [146] concluded that despite radioligand high lipophilicity, the cationic form excluded radiotracer passage through the blood–brain barrier and allowed for peripheral tissue imaging only.…”
Section: Nk1r Radioligands In Nuclear Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…First generation radiotracers were selected from many lead structures, based upon autoradiographic studies of NK1Rs. These compounds were initially investigated in vivo for their ability to be taken up by the brain and other organs in animal models [146,147,148,149] (Figure 4). Early evaluation of [ 11 C]CP-96,345 [146] concluded that despite radioligand high lipophilicity, the cationic form excluded radiotracer passage through the blood–brain barrier and allowed for peripheral tissue imaging only.…”
Section: Nk1r Radioligands In Nuclear Medicinementioning
confidence: 99%
“…These compounds were initially investigated in vivo for their ability to be taken up by the brain and other organs in animal models [146,147,148,149] (Figure 4). Early evaluation of [ 11 C]CP-96,345 [146] concluded that despite radioligand high lipophilicity, the cationic form excluded radiotracer passage through the blood–brain barrier and allowed for peripheral tissue imaging only. PET detection of central and peripheral NK1R occupancy was performed later on hamsters using [ 11 C]CP-99,994 [147] and pigs using [ 11 C]CP-643,051 [148].…”
Section: Nk1r Radioligands In Nuclear Medicinementioning
confidence: 99%
“…However, the compounds cannot be used for detecting changes in substance P levels due to slow dissociation from the receptor. Most attempts to develop in vivo NK 1 -receptor radioligands have been unsuccessful or indifferent, except for the two ligands mention above [23-26]. …”
Section: Introductionmentioning
confidence: 99%
“…A few radioligands have been synthesized for PET or SPECT studies of NK1 receptors (Figure 1). The first ones had quinuclidine {[ 11 C]CP-96,345 (17,18) and [ 125 I]L 703606 (19)} or piperidine structures {[ 11 C]CP-99,-994 (20), [ 18 F]FTP (21), [ 11 C]GR 203040 (22), [ 11 C]GR 205171 (22), [ 18 F]L 829,165 (23), and [ 11 C]CP-643,051 (24)}. More recently, a tryptophan derivative {[ 11 C]LY 303870 (25)} and a substituted piperazine {[ 11 C]R 116301 (26)} were also described.…”
Section: Introductionmentioning
confidence: 99%
“…The search for highly selective radioligands as well as the development of a unique tracer for PET and SPECT is still needed. This challenge requires the presence, in the same structure, of atoms (C, F, I, Br) that can be substituted for their positron ( 11 C, 18 F, 77 Br) or gamma ( 123/125 I) isotope. In 1995, Takeda company described a series of 6-pyrido [3,4-b]pyridinecarboxamide derivatives as a novel class of highly potent, selective, and orally active NK1 receptor antagonists (Figure 2) (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%